Evaluating Uganda's Compliance with the Paris Climate Agreement - Sheilah Nasasira (Uganda Christian University, 2025)
Environmental law plays a crucial role in sustainable development by ensuring the protection, conservation, and responsible use of natural resources. Uganda’s commitment to global environmental governance faces significant implementation challenges despite ratifying key agreements like the Paris Climate Agreement . This research evaluates Uganda’s compliance with international climate obligations, examining the legal and policy barriers to effective adoption of global frameworks. Focusing on the Paris Agreement and how it has been adopted into the national legal framework. This research analyses Uganda’s adoption of four core principles, centred around the Paris Climate Agreement, mainly, the precautionary principle, polluter-pays doctrine, sustainable development, and intergenerational equity, into domestic law through the National Environment Act Cap 181 and the National Climate Change Act Cap. 182. This study analyses treaties to highlight three critical gaps in Uganda’s adherence to the Paris Climate Agreement: legislative inconsistencies between economic priorities and climate commitments, limited institutional capacity for implementation, and enforcement failures in Uganda’s compliance rate with its Nationally Determined Contributions (NDCs). Findings indicate that, while Uganda has developed advanced legal frameworks, challenges like bureaucratic issues and insufficient climate financing undermine compliance. This study identifies key legal, policy, and institutional failures, such as the National Environment Management Authority (NEMA) and Kampala City Council Authority (KCCA), among others, that hinder Uganda’s full compliance with the Paris Climate Agreement 2016. In response, it proposes reforms such as harmonising existing environmental laws with international climate objective treaties, establishing specialised environmental tribunals that act promptly, and strengthening national institutions to implement Uganda’s commitments under the Paris Agreement. These insights will benefit policymakers, legal practitioners, scholars, and environmental advocates in shaping more effective environmental laws and policies.
Undergraduate Research